2022
DOI: 10.1111/bjso.12594
|View full text |Cite
|
Sign up to set email alerts
|

Do we fail to exert self‐control because we lack resources or motivation? Competing theories to explain a debated phenomenon

Abstract: Exerting effort in a first task can impair self-control performance in a subsequent task. Hundreds of studies have examined this ego depletion effect, but the underlying mechanisms are still unknown. By contrasting the two most prominent models, the strength model and the process model, the following question takes centre stage: Do participants fail to exert self-control because they run short of an unspecified resource or because they lack the motivation to engage in the subsequent task? We contrasted competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Friese, Loschelder, Gieseler, Frankenbach and Inzlicht (2019) investigated the highly debated question whether ego depletion is real or not in a literature review and concluded that the available evidence is inconclusive and that more empirical research as well as more theoretical works are needed. Both Gieseler, Loschelder, Job and Friese (2021) as well as Troll, Friese and Loschelder (2023) recently showcased in empirical research that ego depletion effects are in fact not caused by a lack of motivation, but rather by the depletion of mental and volitional resources as proposed by the strength model of self-control. Baumeister (2019) argues that ego depletion is indeed a very real phenomenon and that many of the null findings in prior studies likely resulted from inefficient manipulation of the independent variable or insufficient operationalisation of the core constructs.…”
Section: Self-control Research: Scales Instances Of Moderation Theore...mentioning
confidence: 96%
“…Friese, Loschelder, Gieseler, Frankenbach and Inzlicht (2019) investigated the highly debated question whether ego depletion is real or not in a literature review and concluded that the available evidence is inconclusive and that more empirical research as well as more theoretical works are needed. Both Gieseler, Loschelder, Job and Friese (2021) as well as Troll, Friese and Loschelder (2023) recently showcased in empirical research that ego depletion effects are in fact not caused by a lack of motivation, but rather by the depletion of mental and volitional resources as proposed by the strength model of self-control. Baumeister (2019) argues that ego depletion is indeed a very real phenomenon and that many of the null findings in prior studies likely resulted from inefficient manipulation of the independent variable or insufficient operationalisation of the core constructs.…”
Section: Self-control Research: Scales Instances Of Moderation Theore...mentioning
confidence: 96%
“…The Strength Model of Self‐control also suggests that trait self‐control may be an important moderator of the ego‐depletion effect in adolescents (Baumeister et al, 2018; De Ridder et al, 2012; Troll et al, 2023). For instance, Wills et al (2011) have demonstrated that trait self‐control plays a moderating role in the contagion of drinking behaviors in adolescents and the relationship between peer drinking and instigated episodic drinking is lower in individuals with high trait self‐control.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying participants need to appraise the situation in which bullying occurs and its relevance and potential impact, and then select the most appropriate response among multiple possible choices (Rosen et al, 2016). In this case, a large amount of attentional and cognitive resources would be allocated to appraise the situation, suppress unwanted thoughts, and formulate appropriate responses (Balan et al, 2022; Falla et al, 2022), leading to ego depletion and therefore leaving less self‐control resources for subsequent behaviors (Troll et al, 2023). The bullying episode would be more depleting when the bully is a friend of the participant because of the conflict between peer pressure and social norms (Prinstein & Giletta, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation